The Beginning of the Registration of Estonian Books in Printed Works as Compared with that of the Other Nations of the Baltic Sea - Aarma, Liivi (Knygotyra, 2024)
Jam Amos Comenius described the relation between the world and book in following words: the world is a maze, from which the books can lead us out. The idea can be further developed if we claim that the maze of the realm of books can be solved by technological means of bibliography. Every new step in technology could be described as an annual ring of tree growth, as concentricity. The advent of typography favoured publishing of books and bibliographies in national languages - the same holds true also in comparative treatment of national printed works in Baltic Sea region.We could point out that the bibliography in the countries surrounding Baltic Sea has developed according to general regularity, more or less synchronically. Here l would emphasise that it is the historical phenomenon of networking, much similar to that of modem computer networks. Despite the fact that the fruits of typography were accessible only for quite a limited part of the society the ideas and models spread everywhere, evoking analogous phenomena in various countries and places.Historical national bibliography is highly valued by Polish bibliographers Anna Migon and Marta Skalska-Zlat, who emphasise the contribution it has given to the research and representation of modem national literature.
Keywords: -